Familial Short Stature-A Novel Phenotype of Growth Plate Collagenopathies - Plachy, Lukas; Dusatkova, Petra; Maratova, Klara; Petruzelkova, Lenka; Elblova, Lenka; Kolouskova, Stanislava; Snajderova, Marta; Obermannova, Barbora; Zemkova, Dana; Sumnik, Zdenek; Lebl, Jan; Pruhova, Stepanka (The Journal of clinical endocrinology and metabolism, 2021)
CONTEXT: Collagens are the most abundant proteins in the human body. In a growth plate, collagen types II, IX, X, and XI are present. Defects in collagen genes cause heterogeneous syndromic disorders frequently associated with short stature. Less is known about oligosymptomatic collagenopathies. OBJECTIVE: This work aims to evaluate the frequency of collagenopathies in familial short stature (FSS) children and to describe their phenotype, including growth hormone (GH) treatment response. METHODS: Eighty-seven FSS children (pretreatment height ≤ -2 SD both in the patient and his or her shorter parent) treated with GH were included in the study. Next-generation sequencing was performed to search for variants in the COL2A1, COL9A1, COL9A2, COL9A3, COL10A1, COL11A1, and COL11A2 genes. The results were evaluated using American College of Medical Genetics and Genomics guidelines. The GH treatment response of affected children was retrospectively evaluated. RESULTS: A likely pathogenic variant in the collagen gene was found in 10 of 87 (11.5%) children. Detailed examination described mild asymmetry with shorter limbs and mild bone dysplasia signs in 2 of 10 and 4 of 10 affected children, respectively. Their growth velocity improved from a median of 5.3 cm/year to 8.7 cm/year after 1 year of treatment. Their height improved from a median of -3.1 SD to -2.6 SD and to -2.2 SD after 1 and 3 years of therapy, respectively. The final height reached by 4 of 10 children differed by -0.67 to +1.0 SD and -0.45 to +0.5 SD compared to their pretreatment height and their affected untreated parent's height, respectively. CONCLUSION: Oligosymptomatic collagenopathies are a frequent cause of FSS. The short-term response to GH treatment is promising.
Keywords: Growth Plate; Young Adult; genetické asociační studie; fenotyp; Male; Phenotype; retrospektivní studie; Child, Preschool; růstová ploténka; growth hormone treatment; mladý dospělý; Databases, Factual; Adolescent; Genetic Association Studies; collagenopathies; growth plate; Česká republika; Child; next-generation sequencing; dítě; databáze faktografické; Adult; dospělí; Growth Disorders; kolagen; mužské pohlaví; Collagen Type XI; familial short stature; poruchy růstu; mladiství; Czech Republic; předškolní dítě; lidé; ženské pohlaví; Humans; Collagen; Human Growth Hormone; kolagen typ XI; Retrospective Studies; lidský růstový hormon; Female